Ali-Dede Bosniak on the Origin of the Arabic Language: According to His Work Muḥāḍara al-ʼawāʼil wa musāmara al-ʼawāḫir (Prilozi za orijentalnu filologiju, 2021)
In his famous work Muḥāḍara al-ʼawāʼil wa musāmara al-ʼawāḫir, Ali-dede Bosniak pays considerable attention to cultural and historical topics such as art, language, literature, interpersonal relations and customs. At the very beginning of his work, Ali-dede explores the question of the origin and character of human language, paying special attention to Arabic language, considering it a primordial, divine and fundamental language of humanity. His considerations are focused on the question of the origin and status of Arabic language, as well as on its historical or diachronic development. The much talked about period is the time before the influence of Arabic poetry and the Qur’an, which goes far back in time and where it is difficult to discern what is truth and what is a myth. To make it easier to present, analyze and understand Ali-dede’s idea of the origin and importance of Arabic language, we will try to present it through several basic questions that this author considers in his work.